A pilot trial of deferiprone in pantothenate kinase-associated neurodegeneration patients - Rohani, Mohammad (Neurol Int, 2018)
Pantothenate kinase-associated neurodegeneration (PKAN) is the most common form of neurodegeneration with brain iron accumulation, it is an autosomal recessive disease due to mutation in PANK 2 on chromosome 20, which causes the accumulation of iron in basal ganglia and production of free radicals that cause degeneration of the cells. Deferiprone is an iron chelator that was used in treatment of thalassemia patients, it can cross the blood-brain barrier and reverse the iron deposition in the brain. Five patients with genetically confirmed PKAN received 15 mg/kg deferiprone twice daily. All patients were examined at baseline, 12 and 18 months and magnetic resonance imaging (MRI) was done at the baseline and after 18 months. In our study qualitative evaluation of MRI showed that deferiprone was able to reduce the iron load in globus pallidus of all the patients and the results of clinical rating scales show that in four patients, there is an improvement in the first 12 months. The results of our paper show that deferiprone can prevent the progression of the disease.